sonic hedgehog and vascular endothelial growth factor Act Upstream of the Notch Pathway during Arterial Endothelial Differentiation - Lawson, Nathan D.; Vogel, Andreas M.; Weinstein, Brant M. (Developmental cell, 2002)
The appearance of molecular differences between arterial and venous endothelial cells before circulation suggests that genetic factors determine these cell types. We find that vascular endothelial growth factor (vegf) acts downstream of sonic hedgehog (shh) and upstream of the Notch pathway to determine arterial cell fate. Loss of Vegf or Shh results in loss of arterial identity, while exogenous expression of these factors causes ectopic expression of arterial markers. Microinjection of vegf mRNA into embryos lacking Shh activity can rescue arterial differentiation. Finally, activation of the Notch pathway in the absence of Vegf signaling can rescue arterial marker gene expression. These studies reveal a complex signaling cascade responsible for establishing arterial cell fate and suggest differential effects of Vegf on developing endothelial cells.